Cloud Computing In Higher Education (International Journal of Innovative Research in Computer Science & Technology, 2021)
Information Technology (IT) plays a critical  role in delivering education services to users. To assist  students, professors, researchers, and administrative  personnel, most education online services at universities  have been run on the cloud. These are made possible by the  rise of cloud computing in the IT industry. Cloud computing  provides Internet-based computer services on demand. The  use of cloud computing in higher education, namely tertiary  institutions and universities, is discussed in this article. The  difficulties of cloud computing in higher education are the  subject of the article. It examines studies on adoption  difficulties in higher education institutions and provides  background on cloud computing. These difficulties are  significant because they offer an overview of cloud adoption  in higher education. To study the variables that affect users'  attitudes and behaviors about utilizing The authors  established an integrative references framework based on  difficulties in the research and the TAM model for cloud  educational solutions in schools' ICT offering.
Keywords: Cloud Computing; Data; Education; Information Technology; TAM model